A paper-based colorimetric molecular test for SARS-CoV-2 in saliva - Davidson, Josiah Levi; Wang, Jiangshan; Maruthamuthu, Murali Kannan; Dextre, Andres; Pascual-Garrigos, Ana; Mohan, Suraj; Putikam, Sai Venkata Sravan; Osman, Fujr Osman Ibrahim; McChesney, Darby; Seville, Jordan; Verma, Mohit S. (Biosensors and bioelectronics. X, 2021)
Herein, we describe the development of a paper-based device to detect nucleic acids of pathogens of interest in complex samples using loop-mediated isothermal amplification (LAMP) by producing a colorimetric response visible to the human eye. To demonstrate the utility of this device in emerging public health emergencies, we developed and optimized our device to detect SARS-CoV-2 in human saliva without preprocessing. The resulting device was capable of detecting the virus within 60 min and had an analytical sensitivity of 97% and a specificity of 100% with a limit of detection of 200 genomic copies/μL of patient saliva using image analysis. The device consists of a configurable number of reaction zones constructed of Grade 222 chromatography paper separated by 20 mil polystyrene spacers attached to a Melinex® backing via an ARclean® double-sided adhesive. The resulting device is easily configurable to detect multiple targets and has the potential to detect a variety of pathogens simply by changing the LAMP primer sets. •Paper-based device utilizes RT-LAMP to detect SARS-CoV-2.•Extraction-free detection of SARS-CoV-2 in whole saliva with minimal processing.•Primer sets target the orf7a, orf7b, and orf1ab regions of SARS-CoV-2.•Configurable reaction zones enable multiplexed detection of pathogens.